Patterns of computed tomography surveillance in survivors of colorectal cancer at Veterans Health Administration facilities. Issue 12 (17th February 2017) - Sehdev, Amikar; Sherer, Eric A.; Hui, Siu L.; Wu, Jingwei; Haggstrom, David A.
Abstract : BACKGROUND: Annual computed tomography (CT) scans are a component of the current standard of care for the posttreatment surveillance of survivors of colorectal cancer (CRC) after curative‐intent resection. The authors conducted a retrospective study with the primary aim of assessing patient, physician, and organizational characteristics associated with the receipt of CT surveillance among veterans. METHODS: The Department of Veterans Affairs Central Cancer Registry was used to identify patients diagnosed with AJCC collaborative stage I to III CRC between 2001 and 2009. Patient sociodemographic and clinical (ie, CRC stage and comorbidity) characteristics, provider specialty, and organizational characteristics were measured. Hierarchical multivariable logistic regression models were used to assess the association between patient, provider, and organizational characteristics on receipt of 1) consistently guideline‐concordant care (at least 1 CT every 12 months for both of the first 2 years of CRC surveillance) versus no CT receipt and 2) potential overuse (>1 CT every 12 months during the first 2 years of CRC surveillance) of CRC surveillance using CT. The authors also analyzed the impact of the 2005 American Society of Clinical Oncology update in CRC surveillance guidelines on care received over time. RESULTS: For 2263 survivors of stage II/III CRC who were diagnosed after 2005, 19.4% of patients received no surveillance CT, whereas potential overuse occurred in both surveillance years for 14.9% of patients. Guideline‐concordant care was associated with younger age, higher stage of disease (stage III vs stage II), and geographic region. In adjusted analyses, younger age and higher stage of disease (stage III vs stage II) were found to be associated with overuse. There was no significant difference in the annual rate of CT scanning noted across time periods (year ≤ 2005 vs year > 2005). CONCLUSIONS: Among a minority of veteran survivors of CRC, both underuse and potential overuse of CT surveillance were present. Patient factors, but no provider or organizational characteristics, were found to be significantly associated with patterns of care. The 2005 change in American Society of Clinical Oncology guidelines did not appear to have an impact on rates of surveillance CT. Cancer 2017;123:2338–2351. © 2017 American Cancer Society . Abstract : Among a minority of veterans who are survivors of colorectal cancer, both a lack of guideline‐concordant computed tomography surveillance and potential overuse appear to be present. Patient factors, but not provider or organizational characteristics, are significantly associated with guideline‐concordant care. The 2005 change in the American Society of Clinical Oncology guidelines does not appear to have had an impact on rates of surveillance computed tomography.